Conflict and resource control in the Niger Delta: Implications for the Gulf of Guinea Region - Felix Ifeanyichukwu Igbeke (African Journal of Environmental Economics and Management, 2018)
Gaps between the definition of expectations, grants of power and verification of accruals from resources, especially oil and gas, tend to undergird the governance processes in most states that comprise the Gulf of Guinea. These gaps have been responsible for the various problems that have become part of, and which have engendered violence and conflict in the region. As a major stakeholder in the politics and economic strength of the Gulf of Guinea, Nigeria seems to be responsible for the continued crisis in the region. The study, using a coalescence of theoretical explications for understanding the resource-conflict thesis, notes that misgovernance by Nigeria as a major stakeholder and one of the most endowed countries in the region negatively affects the wider Gulf of Guinea region; this negativity is manifested in the now-seeming intractable conflict in the region, and thus makes a case for a thorough understanding of the implications for both Nigeria and the wider Gulf of Guinea region in order to resolve the conflict in the African continent.